SAT0475 Locus of control of pain in patients with knee osteoarthritis - Nunez, M; Nunez, E; Lozano, L; Sastre, S; Saulo, A; Nicodemo, C; Segur, J; Suso, S (BMJ Publishing Group, 2014)
Knee osteoarthritis (OA) is a degenerative joint disease in which pain and disability tend to increase in parallel with the disease duration. As in other chronic diseases, pain togetherwith functional disability supposes not only a reduced quality of life but also the need for sufferers to adapt. The importance of the concept of locus of control, i.e. the belief in the possibility and/or ability to control symptoms and achieve and maintain a specific level of health, has been suggested in patients with chronic pain.